GluN2B-containing NMDA receptor attenuated neuronal apoptosis in the mouse model of HIBD through inhibiting endoplasmic reticulum stress-activated PERK/eIF2α signaling pathway - Wu, Mengxue; Xu, Shilian; Mi, Kai; Yang, Shuang; Xu, Yuanyuan; Li, Jie; Chen, Junyang; Zhang, Xiaomin (Frontiers in Molecular Neuroscience, 2024)
Neonatal hypoxic-ischemic brain damage (HIBD) refers to brain damage in newborns caused by hypoxia and reduced or even stopped cerebral blood flow during the perinatal period. Severe cases can lead to death, and most survivors suffer from severe neurological sequelae, such as cerebral palsy, epilepsy, and intellectual disability.Currently, there are no targeted treatments for neonatal ischemic hypoxic brain damage, primarily due to the incomplete understanding of its pathophysiological mechanisms.The role of NMDA receptors, which mediate excitotoxicity in cerebral ischemia, is less studied in HIBD. In this study, we explored the mechanism of endogenous protection by GluN2B-NMDAR in HIBD. GluN2B-NMDAR, a dominant NMDA receptor subtype highly expressed in the early developmental brain, exerts neuroprotective effects through the PI3K/Akt/CREB signaling pathway. Hypoxic-ischemic events lead to energy depletion, causing endoplasmic reticulum stress and activating the downstream UPR signaling pathway. Prolonged activation of the UPR pathway can lead to apoptosis. We found that GluN2B-NMDAR regulates the PERK/eIF2α signaling pathway to inhibit apoptosis. After selective inhibiting GluN2B-NMDAR in HIBD mice with ifenprodil, the PERK/eIF2α signaling pathway remains continuously activated, leading to neuronal apoptosis, morphological brain damage, and aggravating deficits in spatial memory, cognition, and social abilities in mice. These results indicate that, unlike its role in adult brain damage, GluN2B in early development plays a neuroprotective role in HIBD by inhibiting excessive activation of the PERK/eIF2α signaling pathway.This study provides theoretical support for the clinical development of targeted drugs or treatment methods for HIBD.